Theoretical and methodological evaluation aspects of intellectual capital construction enterprises - Yashchenko, V. (Ways to Improve Construction Efficiency, 2015)
In the article it was explained the priority of definition, evaluation and development questions of intellectual capital of construction companies as the most important advantage of them in the competition. It was organized of existing theoretical and methodological aspects of intellectual capital evaluation for modern construction companies, given their specifics.